Production of innovative hemp based three-layered particleboards with reduced raw densities and low formaldehyde emissions. (13th August 2009) - Schopper, Christian; Kharazipour, Alireza; Bohn, Christian
The possibility to substitute wood by hemp for the production of wood based panels and the possibility to produce lightweight panels by using hemp are the main research focuses of this project. The regular density of three-layered particleboards (650 kg/m³) shall be decreased to less than 400 kg/m³ by the utilisation of hemp. Another quite interesting aspect that we want to analyse in line with this project is to reduce the formaldehyde emissions of urea-formaldehyde-, melamine formaldehyde- orphenol-formaldehyde-resin bonded wood based panels by using natural binder systems such as proteins and starches.